2017
DOI: 10.1074/jbc.m117.789446
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of side-chain partitioning of β-signal residues in unassisted folding of a transmembrane β-barrel protein

Abstract: The free energy of water-to-interface amino acid partitioning is a major contributing factor in membrane protein folding and stability. The interface residues at the C terminus of transmembrane β-barrels form the β-signal motif required for assisted β-barrel assembly in vivo but are believed to be less important for β-barrel assembly in vitro. Here, we experimentally measured the thermodynamic contribution of all 20 amino acids at the β-signal motif to the unassisted folding of the model β-barrel protein PagP.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(108 citation statements)
references
References 82 publications
(170 reference statements)
6
101
1
Order By: Relevance
“…PagP possesses 12 tryptophans that are distributed throughout the protein. We and others have observed that PagP exhibits hysteresis or incomplete unfolding in alkaline conditions in lipid vesicles ( 20 , 22 ). Hence, we examined only the folding titration of the equilibrium reaction in small unilamellar vesicles (SUVs) of 1,2-dilauroyl- sn -glycero-3-phosphocholine (DLPC), as reported previously ( 20 ).…”
Section: Methodsmentioning
confidence: 79%
See 4 more Smart Citations
“…PagP possesses 12 tryptophans that are distributed throughout the protein. We and others have observed that PagP exhibits hysteresis or incomplete unfolding in alkaline conditions in lipid vesicles ( 20 , 22 ). Hence, we examined only the folding titration of the equilibrium reaction in small unilamellar vesicles (SUVs) of 1,2-dilauroyl- sn -glycero-3-phosphocholine (DLPC), as reported previously ( 20 ).…”
Section: Methodsmentioning
confidence: 79%
“…We and others have observed that PagP exhibits hysteresis or incomplete unfolding in alkaline conditions in lipid vesicles ( 20 , 22 ). Hence, we examined only the folding titration of the equilibrium reaction in small unilamellar vesicles (SUVs) of 1,2-dilauroyl- sn -glycero-3-phosphocholine (DLPC), as reported previously ( 20 ). Briefly, we added 5 μ g/ μ L (0.26 mM) unfolded PagP in a 1:9 ratio to 8.9 mM DLPC SUVs to generate a folding stock containing 26 μ M protein and 8 mM lipid dissolved in 4.5 M GdnHCl prepared in 20 mM Tris-Cl (pH 9.5) and 20 mM 1,4-dithiothreitol (DTT).…”
Section: Methodsmentioning
confidence: 79%
See 3 more Smart Citations